Geometry Problem. Post your solution in the comment box below.
Level: Mathematics Education, High School, Honors Geometry, College.
Click the figure below to view more details of problem 1284.
Monday, November 7, 2016
Geometry Problem 1284 Two Equilateral Triangle, Midpoint, Congruence
Labels:
congruence,
equilateral,
midpoint,
triangle
Subscribe to:
Post Comments (Atom)
https://goo.gl/photos/49eNJ5Yuiq4nrZ5P8
ReplyDeleteDraw M on BF such that FM=FB ( see sketch)
We have triangle ACM is equilateral
Triangle ACE congruent to MCD ( case SAS)
And triangle MCD is the image of ACE in the rotational transformation center at C, rot. Angle= 60 degrees.
So AE=MD and angle(AE, MD)= 60
And FH=1/2.AE and FH//AE
FG=1/2.MD and FG//MD
So FG=GH and angle(FG, FH)= angle (AE,MD)= 60 degrees
And FGH is equilateral
Problem 1284
ReplyDeleteLet the equilateral triangle AEP (PA,PE intersects the BD, not the extensions ). Then triangle ABP=triangle ACE (AB=AC,AP=AE, <BAP=60-<PAC=<CAE).So BP=CE=CD,but
<PBC+<BCD=<ABP-60+<BCD=<ACE-60+<BCD=240-60=180, then BP//CD so the BPDC is
Parallelogram .Then the points P,G and C are collinear with PG=GC.So GF=AP/2=AE/2=FH
and <HFG=<EAP=60 (GF//AP,FH//AE).Therefore triangle FGH is equilateral.
APOSTOLIS MANOLOUDIS 4 HIGH SCHOOL KORYDALLOS PIRAEUS GREECE
Complete the rhombus ABCX.
ReplyDeleteTriangles ACE ≡ XCD, SAS.
So AE = XD and hence FH = FG from the mid point theorem in triangles ACE
and XBD.
Similarly we can show that GH = FH by completing rhombus CDEY.
Hence FG = FH = GH
Sumith Peiris
Moratuwa
Dear Antonio
ReplyDeleteMy solution does not appear yet, hence resenting.
Complete the rhombus ABCX.
Triangles ACE ≡ XCD, SAS.
So AE = XD and hence FH = FG from the mid point theorem in triangles ACE
and XBD.
Similarly we can show that GH = FH by completing rhombus CDEY.
Hence FG = FH = GH
Sumith Peiris
Moratuwa
Sri Lanka